The Determinants Of Electronic Health Record Adoption And The Role Of Data Governance As Mediator In Indonesia - Said, Ahmad (2024)
Electronic health records (ehrs) can transform healthcare delivery by promoting patient care, decreasing costs, co-integration relationships, and creating new ecosystem healthcare technology. It is urgent to address significant determinants contributing to ehr adoption in indonesia; hence, this study investigates the mediation of data governance that may affect the adoption of ehrs. The primary objective of this study is to elucidate the role of data governance in mediating the adoption of electronic health records (ehrs) within the context of challenges associated with data standardisation and integration across public hospitals in indonesia. This quantitative study explores the technological, organisational, and environmental aspects that influence ehr adoption and evaluates the impact of data governance on ehr adoption. To understand the symbiosis of technologyorganisation- environment framework (toe), diffusion of innovation (doi) theory, and data governance framework, this study examined the relationship between technology characteristic (tc), technology availability (ta), formal-informal linking organisation (fi), top management support (tm), slack (sl), hospital size (sz), competitive pressure (cp), infrastructure (if), data governance (dg), and ehrs adoption.